Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-demos.8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Literature Knowledge Graph Construction and Drug Repurposing Report Generation

Abstract: To combat COVID-19, both clinicians and scientists need to digest vast amounts of relevant biomedical knowledge in scientific literature to understand the disease mechanism and related biological functions. We have developed a novel and comprehensive knowledge discovery framework, COVID-KG to extract finegrained multimedia knowledge elements (entities and their visual chemical structures, relations and events) from scientific literature. We then exploit the constructed multimedia knowledge graphs (KGs) for que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…Pham et al proposed a deep learning method, namely DeepCE, to model substructure-gene and gene-gene associations for predicting the differential gene expression profile perturbed by de novo chemicals, and demonstrated that DeepCE outperformed state-of-the-art, and could be applied to COVID-19 drug repurposing of COVID-19 with clinical evidence [63]. Zhou et al provided a useful review and helpful illustrations of these machine learning, and AI techniques for COVID-19 drug repurposing [91] The knowledge graph does not have to be manually constructed, except for the existing biological datasets, as machine learning and natural language processing (NLP) techniques are appropriate tools to automatically construct knowledge graphs from scientific literature [65].…”
Section: Mining Patient Data and Drug Repurposingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pham et al proposed a deep learning method, namely DeepCE, to model substructure-gene and gene-gene associations for predicting the differential gene expression profile perturbed by de novo chemicals, and demonstrated that DeepCE outperformed state-of-the-art, and could be applied to COVID-19 drug repurposing of COVID-19 with clinical evidence [63]. Zhou et al provided a useful review and helpful illustrations of these machine learning, and AI techniques for COVID-19 drug repurposing [91] The knowledge graph does not have to be manually constructed, except for the existing biological datasets, as machine learning and natural language processing (NLP) techniques are appropriate tools to automatically construct knowledge graphs from scientific literature [65].…”
Section: Mining Patient Data and Drug Repurposingmentioning
confidence: 99%
“…More specifically, Chen et al combined the CORD-19 dataset [64] and the PubMed dataset [73] to identify COVID-19-related experts and bio-entities [69]. Another example is the COVID-KG framework, which could extract fine-grained multimedia knowledge elements from scientific literature [65]. The resulted knowledge is available at http://blender.cs.…”
Section: Mining Scientific Literaturementioning
confidence: 99%
“…As this dataset was designed for a particular cause, it is biased towards the biological and medial fields. The research output of the COVID19 dataset is extensive, including document summerisation [7], drug re-purposing [8] and risk factor identification [9]. A comprehensive overview will take a review article in itself to summarise this contribution.…”
Section: Related Workmentioning
confidence: 99%
“…There exist several representatives and comprehensive KGs, such as IBM Watson, 22 SNOMED‐CT, 23 and CmeKG, 24 and so forth, most of which aimed to save time and vigour, alleviate the pressure of physicians, and improve the accuracy of diagnosis to some extent. By investigation, the existing professional medical KGs mainly focus on diseases, 25 drugs, 26 cells, 27 literature, 28,29 proteins, genes, and organs 28 . However, personal lifestyles such as diet, sleep, vitamins, and environment, which are critical triggers of diseases, such as prostate cancer (PCa), can be an inspiration for novel direction in this field 30 …”
Section: Introductionmentioning
confidence: 99%